Broadband absorption enhancement in ultra‐thin crystalline Si solar cells by incorporating metallic and dielectric nanostructures in the back reflector. (19th July 2014) - Jain, Samarth; Depauw, Valerie; Miljkovic, Vladimir D.; Dmitriev, Alexander; Trompoukis, Christos; Gordon, Ivan; Van Dorpe, Pol; El Daif, Ounsi
Abstract: We propose a back reflecting scheme in order to enhance the maximum achievable current in one micron thick crystalline silicon solar cells. We perform 3D numerical investigations of the scattering properties of metallic nanostructures located at the back side and optimize them for enhancing absorption in the silicon layer. We validate our numerical results experimentally and also compare the absorption enhancement in the solar cell structure, both with quasi‐periodic and random metallic nanostructures. We have looked at the interplay between the metallic nanostructures and an integrated back reflector. We show that the combination of metallic nanoparticles and a metallic reflector results in significant parasitic absorption. We compared this to another implementation based on titanium dioxide nanoparticles, which act as a Lambertian reflector of light. Our simulation and experimental results show that this proposed configuration results in reduced absorption losses and in broadband enhancement of absorption for ultra‐thin solar cells, paving the way to an optimal back reflector for thin film photovoltaics. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : The back reflecting scheme of a c‐Si ultrathin solar cell was optimized using both metallic and dielectric nanoparticles. During optimisation, a focus was made on light trapping in the red part of the spectrum. As a result, the absorption of a 1micron thick c‐Si slab is enhanced by more than 60%.